2012
DOI: 10.1016/j.jpainsymman.2011.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality of Pain Care in Ambulatory Patients With Advanced Stage Cancer

Abstract: There is room for improvement in the pain care of patients with advanced cancer. Additional research is needed to understand the reasons for poor performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Yet, they did not objectively study medical records, but they asked patients whether the doctor assessed pain. The figures in our study are in accordance with a study of Weingart et al., who found that pain assessment in ambulatory patients with cancer was insufficient. Obviously, the clinical practice guideline has not been implemented in the working method of medical oncologists in the participating hospitals.…”
Section: Discussionsupporting
confidence: 93%
“…Yet, they did not objectively study medical records, but they asked patients whether the doctor assessed pain. The figures in our study are in accordance with a study of Weingart et al., who found that pain assessment in ambulatory patients with cancer was insufficient. Obviously, the clinical practice guideline has not been implemented in the working method of medical oncologists in the participating hospitals.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to analgesics, effective management of cancer pain also depends on clinicians having a flexible approach and detailed knowledge regarding the range of available analgesic options and preparations. Undertreatment is usually attributed to inappropriate opioid use, which results from factors that can pertain to patients, family, institutions, society and even healthcare providers ( 5 ). Since unresolved pain detrimentally affects physical functioning, psychological well-being and social interaction ( 6 ); education and occupational guidelines are integral to the achievement of better pain control.…”
Section: Introductionmentioning
confidence: 99%
“…The Institute of Medicine reported that 50% of cancer patients around the world had pain. 22 In USA, Weingart 23 examined the quality of cancer pain care and reported that among advanced cancer patients with severe pain, 34% of patients continued to report severe pain a month after the visit. In Italy, 40.3% of cancer patient with pain had breakthrough pain, but most of them being untreated did not.…”
Section: Undertreatment Of Cancer Painmentioning
confidence: 99%